Pengembangan E-LKPD Interaktif Materi Teks Cerita Pendek Berbasis Website Wizer.me Kelas XI SMA Tahun Pembelajaran 2022/2023 - Cordellia Alfitrina Sitanggang; Fitriani Lubis (Medan Resource Center, 2023)
This study aims to determine the development procedures, forms, and feasibility of interactive E-LKPD short story text material based on the Wizer.me website for class XI SMA in the 2022–2023 Academic Year. The development model used in this research is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The e-LKPD feasibility test is based on the results of the material expert validator's assessment, the media expert validator's assessment, the Indonesian language teacher's assessment, and student responses. The results of the assessment obtained from the validation of material experts show that the E-LKPD has the status of